Transforming growth factor serum concentrations in patients with proven non-syndromic aortopathy - Karalko, Mikita; Pojar, Marek; Zaloudkova, Lenka; Stejskal, Vaclav; Timbilla, Salifu; Brizova, Pavla; Vojacek, Jan (Frontiers in Cardiovascular Medicine, 2022)
Background The mechanism underlying aortic dilatation is still unknown. Vascular dilatation is thought to be the result of progressive aortic media degeneration caused by defective vascular matrix hemostasis, including TGF- β1 dysregulation. The goal of this study is to draw attention to the potential utility of TGF- β1 as a diagnostic marker in non-syndromic patients with aortic dilatation. Methods TGF- β1 levels in plasma were measured in 50 patients who had undergone surgery and had a tricuspid or bicuspid aortic valve as well as a normal or dilated ascending aorta. A pathologist also examined thirty resected aorta samples. To specify the reference range of TGF- β1, a control group of 40 volunteers was enrolled in this study. Results We discovered a significant difference in TGF- β1 levels between patients with aortic dilatation and the control group (32.5 vs. 63.92; P<0.001), as well as between patients with non-dilatated aorta but with aortic valve disease, and the control group (27.68 vs. 63.92; P<0.001). There was no difference between the dilatated ascending aorta group and the non-dilatated ascending aorta group. We found a poor correlation between TGF- β1 levels and ascending aorta diameter as well as the grade of ascending aorta histopathological abnormalities. Conclusions TGF- β1 concentration does not meet the criteria to be a specific marker of aortic dilatation, but it is sensitive to aortic valvulopathy-aortopathy. A larger patient cohort study is needed to confirm these findings.